Bionomics of the pied stilt (Himantopus leucocephalus) in New Zealand : with special reference to breeding behaviour: a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Zoology at Massey University - McConkey, Brian F (Massey University, 1971)
Aims of the Study. Although the Pied Stilt, Himantopus h.leucocephalus, Gould,1837*Nomenclature for New Zealand birds follows that laid down in the Annotated Checklist of the Birds of New Zealand (Kinsky,1970). Other bird species are as prescribed in the Handbook of British Birds (Witherby et al, 1943) or in the specific reference works quoted. is one of New Zealand's most common wading birds there has been very little published work on it. The purpose of this study therefore was to gain knowledge of the general biology of the Pied Stilt with special reference to breeding behaviour. It has been suggested (L.Gurr, pers.comm.) that the large numbers of Pied Stilt may be responsible for genetic swamping, through interbreeding, of the Black Stilt Himantopus novaezealandiae Gould, 1841 which is now quite rare and its breeding range restricted to a very small area of New Zealand - the Waitaki River system. The intention was that this study should provide information as a background to further investigation of the problem. This study is based on field observations made between February 1969 and December 1970 in the Manawatu district around Palmerston North, where Pied Stilts are found in large enough numbers to permit relatively easy observation, except during the winter months when their numbers drop considerably.
Keywords: Charadriiformes -- New Zealand; Himantopus leucocephalus; Recurvirostridae; Stilts